Satisfied, but Will They Spread a Word? The Role of Customer Satisfaction at Jamu Café - Usep Suhud; Sheila Maryam Bajunaid (Bina Nusantara University, 2018)
This research aimed to investigate consumers’ intention to repurchase jamu at Jamu Café. Service quality, customer satisfaction, and Word-of-Mouth (WOM) were selected as the predictor variables. In total, 200 participants who purchased jamu at the café were selected conveniently. Data were analyzed using exploratory and confirmatory factor analyses as well as Structural Equation Model (SEM). As a result, service quality influences customer satisfaction significantly. As customers are satisfied, they do word-of-mouth and repurchase. On the other hand, WOM has an insignificant impact on repurchase intention.